Autistic Traits, STEM, and Medicine: Autism Spectrum Quotient Scores Predict Medical Students' Career Specialty Preferences. (October 2021) - Turner, Emma; Aitken, Emma; Richards, Gareth
There is a higher than chance representation of autistic people and people with elevated autistic traits in Science, Technology, Engineering and Mathematics (STEM) industries. Medical students, despite studying a STEM subject, have lower autistic traits than other STEM students. Medicine is heterogenous, covering technique-oriented specialties (e.g., surgery) with little patient interaction, person-oriented specialties (e.g., pediatrics), and general practice. We present an online survey in which 502 UK university students (medicine, n = 344; STEM, n = 94; non-STEM, n = 64) reported their study area and career aspirations and completed the Autism Spectrum Quotient (AQ), a quantitative self-report measure of autistic traits. Our main findings were that medical students had significantly lower AQ scores than other STEM ( p < .001, d = 0.614) and non-STEM students ( p < .001, d = 0.874), and that medical students aiming to pursue technique-focused career paths had significantly higher AQ scores than medical students aiming to pursue person-oriented career paths ( p = .009, d = 0.318). Each of these effects remained statistically significant after adjusting for alpha inflation. The findings of this study corroborate those of previous research reporting a link between autism and STEM; they also provide evidence that autistic traits are a predictor of medical students' career ambitions, with those students with high AQ scores being more likely to pursue technique-focused (as opposed to person-focused) roles. This may be informative for developing and optimizing the strengths of individuals with differing levels of autistic traits.